Talk and sound : audible phenomena and the design of novel technologies for collaboration - de la Flor, G; Jirotka, M (2011)
When designing software for a community of skilled practitioners it is important to understand their requirements for new technological systems. This understanding must inevitably be based upon the ways in which the members of a community themselves organise work activities, communication and collaboration. In the domain of Requirements Engineering we uncover the organisation of work through sociologically-informed methods, particularly ethnomethodology, conversation analysis and interaction analysis. For this poster, we will present the qualitative methods used to understand conversational data within its context of production. Conversation analysis is used to analyse the sequential organisation of talk in order to reveal the ways in which mutual intelligibility is achieved amongst the participants of a setting. Through an analysis of reflexively emerging interaction we not only analyse the sounds produced by co-conversationalists as publicly observable/hearable phenomena but also the language games that link the rules and meaning of language to its situated use and the mechanics of embodied interaction that convey non-verbal or paralinguistic information. Informed by these qualitative approaches software requirements are identified and proof-of-concept prototypes examined for how well technologies may be aligned with the endogenous organisation of work within a community of practice. Examples of detailed naturalistic studies of work and interaction will be presented in the poster from domains as diverse as clinical medicine, stock market trading and palaeography.